Organizational Change: Work Systems and Culture in Private School during the Covid-19 Pandemic (Study at Pelita Nusantara Kasih Christian School Surakarta) - Edith Sarasvianti; Andre Noevi Rahmanto; Ignatius Agung Satyawan (Journal of Social Interactions and Humanities, 2023)
Change is something that often happens in our lives, as well as in an organization. This can be caused by various factors, both internal and external factors.In the pandemic Era The Work from Home and Study from Home policies that issued by the Government brought major changes to Schools. In the process of change, of course there is a process that happened. this study focuses on the process of change that afterward during the COVID-19 pandemic by looking at the old organizational culture before the pandemic into a new culture using Kurt Lewin's theory of change and by using a qualitative approach with descriptive research which is located at Pelita Nusantara Kasih Christian School . The results are that the process of change that occurs both in the work system, and the organizational culture is considered effective because within six months many changes have been made and implemented.